What is in a Name? Parent, Professional and Policy-Maker Conceptions of Consent-Related Language in the Context of Newborn Screening. (4th May 2019) - Nicholls, Stuart G; Etchegary, Holly; Tessier, Laure; Simmonds, Charlene; Potter, Beth K; Brehaut, Jamie C; Pullman, Daryl; Hayeems, Robin Z; Zelenietz, Sari; Lamoureux, Monica; Milburn, Jennifer; Turner, Lesley; et al.
Abstract: Newborn bloodspot screening programs are some of the longest running population screening programs internationally. Debate continues regarding the need for parents to give consent to having their child screened. Little attention has been paid to how meanings of consent-related terminology vary among stakeholders and the implications of this for practice. We undertook semi-structured interviews with parents ( n = 32), healthcare professionals ( n = 19) and policy decision makers ( n = 17) in two Canadian provinces. Conceptions of consent-related terms revolved around seven factors within two broad domains, decision-making and information attainment . Decision-making comprised: parent decision authority; voluntariness; parent engagement with decision-making; and the process of enacting choice. Information ascertainment comprised: professional responsibilities (including disclosure of information and time to review); parent responsibilities; and the need for discussion and understanding prior to a decision. Our findings indicate that consent-related terms are variously understood, with substantive implications for practice. We suggest that consent procedures should be explained descriptively, regardless of approach, so there are clear indications of what is expected of parents and healthcare professionals. Support systems are required both to meet the educational needs of parents and families and to support healthcare professionals in delivering information in a manner in keeping with parent needs.